The impact of cargo bikes on the travel patterns of women. Issue 1 (1st January 2018) - Riggs, William; Schwartz, Jana
ABSTRACT: Research shows a disparity continues to exist between women and men with regard to cycling behavior; women cycle at far lower rates. Cargo bikes have been suggested as one tool to increase the gender balance in bicycle ridership. This research evaluates this suggestion through the lens of: (1) an analysis of survey data regarding cargo bike usage by gender; and (2) interviews with women who use cargo bikes. Data from surveys and interviews explore the influence of cargo bikes on transportation patterns and how behavior, attitude, spatial context, and perception vary between riders. Results show that 78% percent of women used cargo bikes for trips with kids, vs. 56% of men. Qualitative work expands this and suggest that cargo bike use is likely tempered by access to a cargo platform, geography, cultured and rider experience. These results illustrate not only the powerful potential cargo bikes might have in shaping the travel patterns of the future, but also need to address issues in infrastructure and education that may pose impediments to female ridership.